Effect of TGF-β1 on water retention properties of healthy and osteoarthritic chondrocytes. (2018) - Raja, Tehmeena Israr; Khaghani, Seyed Ali; Zafar, Muhammad Sohail; Khurshid, Zohaib; Mozafari, Masoud; Youseffi, Mansour; Sefat, Farshid
Abstract: Osteoarthritis (OA) is a progressive degenerative disease, which includes reduction of cartilage thickness between two bones in a joint, causing painful bone-to-bone contact. OA affects over 8 million people in the UK alone, and as the primary causes are unknown, available treatments only reduce the symptoms instead of providing a cure. This project focused on utilizing TGF-β1, a cytokine found in elevated amounts in healthy cartilage when compared to degraded cartilage, in order to observe the effects of the growth factor on both healthy and osteoarthritic chondrocytes. The healthy and the osteoarthritic chondrocytes were cultured in two different media (DMEM with and without TGF- β1) before utilizing the SpectraMax M2/M2e plate reader to observe and analyze the effect of TGF-β1 on water retention properties of cells. This has been achieved by quantifying the GAG content using DMMB dye. Results showed that although TGF-β1 displayed an increase in glycosaminoglycan synthesis, the statistical increase was not vast enough for the alternative hypothesis to be accepted; further experimentation with TGF-β1, alongside other cytokines within the growth factor family is needed to perceive the true influence of the growth factor on uncured degenerative diseases. It was concluded that both the healthy and osteoarthritic cells treated with TGF-β1 absorbed considerably more DMMB in comparison to the cells, suggesting that TGF-β1 indeed works to aid in water retention.